Basic Guides to officiating - Jones, R. (2008)
Manual for officiating in flatwater canoe racing , version 5 - July 2008 (full text) Table of contents: Introduction and Preface to Version 5 Jury Boat Control - Measuring Starting and Aligning Umpiring Judging and Timekeeping Announcing Technical Organisation Competition Manager Deputy Chief Judge Competition Committee Examination Questions and References